The Estimation of Greenhouse Gas Emissions from the Waste Sector in Lao PDR - Singdala, Outhay; Vannavongsy, Sombane (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
Greenhouse gases (GHGs), such as carbon dioxide (CO2), methane (CH4), nitrous oxide (N2O), and fluorinated gases, are key contributors to global climate change by trapping heat in the Earth's atmosphere. The waste sector, encompassing solid waste disposal, biological treatment, incineration, and wastewater management, is a significant source of GHG emissions. This study aims to assess and quantify GHG emissions from the waste sector in Lao PDR, analyze the contribution of wastewater treatment and discharge to methane emissions, and identify gaps in the current data on waste management emissions. Using the Tier 1 methodology outlined in the 2006 IPCC (Intergovernmental Panel on Climate Change) guidelines, this research evaluates emissions from the waste sector in Lao PDR from 1960 to 2022. The results reveal a total of 1,631.89 GgCO2eq emissions, with methane (CH4) contributing 1,536.25 GgCO2eq, nitrous oxide (N2O) 95.47 GgCO2eq, and carbon dioxide (CO2) 0.17 GgCO2eq. Wastewater treatment and discharge emerge as the primary source of methane emissions, responsible for 980.68 GgCO2eq. Despite these findings, the study identifies significant gaps in data collection, particularly in areas like biological treatment and open burning of waste, which were not comprehensively included. These limitations highlight the need for further research to gather more extensive and accurate data across Lao PDR, especially to better understand the full emissions profile of the waste sector.